The youth work career: Exploring long-term careers of professional youth workers in Western Australia - Sutcliffe, John (2021)
The purpose of this research was to explore the meaning and experiences of the long-term careers of youth workers. This study selected a Western Australian sample group of 10 degreequalified youth workers who had graduated between 1990 and 1999 and had experienced careers in youth work spanning 20 years. The existing literature pertaining to long-term youth work careers was sparse in certain aspects, which established the primary need for the research focus. The related literature was found to represent a negative image of youth work as a career. Youth work was considered lacking in professional identity and was most commonly characterised by burnout, temporary employment prospects and an occupational pathway to other related professions. The deficits and barriers to retention and career longevity prompted the question: How does this explain those individuals who have forged a long-term career in youth work? Two research methods were used in this study: phenomenological inquiry, to seek the shared experiences of the youth work career, and grounded theory methods, to examine the extent to which the self-concept theory of career development and the life career rainbow model could be applied to improve understanding of youth work as a long-term career. The study found important differences in comparison with findings of the existing literature. Participants described careers characteristic of continuous employment; sustainability through supportive connections; longevity through leadership opportunities; and a diverse fusion of opportunities, variety and flexibility in roles undertaken. In stark contrast with the existing literature, these findings led to the development of a synthesised provisional model of the long-term youth work career. Key contributions to knowledge from the study include a constructive representation of the long-term youth work career, with significant factors of longevity being continuous employment, leadership opportunities, diversity in roles and workplaces, and supportive connections. Appraisal of career theory also resulted in suggested revisions to the self-concept theory of career development and the life career rainbow model. A provisional model of the long-term youth work career was developed, which was synthesised from the findings and key discussion points of this study. The provisional model reflected the youth work career as a knowledge-based profession, a distinct practice, a sustainable profession and a long-term career prospect. The findings also have potential implications for the youth field, particularly individual and organisational ethical practice, the importance of workplace and role flexibility, the inclusivity of youth work contexts, and the prioritisation of professional supervision and mentoring